Survival of the minority Kristang language in Malaysia - Mohamed Ali, Haja Mohideen; Mohideen, Shamimah (www.languageinindia.com, 2008)
Kristang, also known as Malaccan Portuguese Creole, is spoken by a microscopic minority of Catholic Christians who are descendants of Portuguese colonizers and Asian settlers in Malacca, a famed port which was coveted by major European powers. Because the very small size of the Kristang community, the language is struggling to survive.Its lexifier is mostly Portuguese as it was used then,with some Malay vocabulary. The minority language may yet be maintained, thanks to the perseverance of the remaining members and the Government which recognizes their distinct identity.